2023
DOI: 10.1002/hpm.3700
|View full text |Cite
|
Sign up to set email alerts
|

The association between mother‐to‐child HIV transmission knowledge and antenatal care utilisation in Cameroon

Abstract: While the health benefits of antenatal care (ANC) utilisation for mothers and their infants have been well documented, very few studies have explored the association between mother‐to‐child transmission (MTCT) knowledge of human immunodeficiency virus (HIV) and mothers' utilisation of ANC in HIV endemic regions such as Cameroon. To address this void in the literature, we use the 2018 Cameroon Demographic and Health Survey to examine the association between mother's knowledge of MTCT of HIV and the three strand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…This is particularly important as an earlier study elsewhere in Cameroon has linked such knowledge to the timely initiation and uptake of antenatal care services that help reduce the chances of vertical transmission. 17 Similarly, Tippett Barr et al 9 found in Malawi that women living with HIV may be initiating ART at later stages during their postpartum periods, although this tends to increase the risk of MTCT of HIV. Emphasising the need for timely initiation of treatment for women living with HIV during pregnancy, van Lettow et al 18 further observed that women who missed any of the recommended steps for the prevention of MTCT of HIV increased their likelihood of vertical transmission.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important as an earlier study elsewhere in Cameroon has linked such knowledge to the timely initiation and uptake of antenatal care services that help reduce the chances of vertical transmission. 17 Similarly, Tippett Barr et al 9 found in Malawi that women living with HIV may be initiating ART at later stages during their postpartum periods, although this tends to increase the risk of MTCT of HIV. Emphasising the need for timely initiation of treatment for women living with HIV during pregnancy, van Lettow et al 18 further observed that women who missed any of the recommended steps for the prevention of MTCT of HIV increased their likelihood of vertical transmission.…”
Section: Introductionmentioning
confidence: 99%